2019
DOI: 10.3847/1538-4357/ab2d27
|View full text |Cite
|
Sign up to set email alerts
|

Presolar Silicon Carbide Grains of Types Y and Z: Their Molybdenum Isotopic Compositions and Stellar Origins

Abstract: We report Mo isotopic compositions of 37 presolar SiC grains of types Y (19) and Z (18), rare types commonly argued to have formed in lower-than-solar metallicity asymptotic giant branch (AGB) stars. Direct comparison of the Y and Z grain data with data for mainstream grains from AGB stars of close-to-solar metallicity demonstrates that the three types of grains have indistinguishable Mo isotopic compositions. We show that the Mo isotope data can be used to constrain the maximum stellar temperatures (T MAX ) d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 83 publications
1
29
0
Order By: Relevance
“…The minor type Y and Z grains (a few % of all SiC grains, depending on grain size), which fall to the 30 Si-rich side of the Si mainstream line, were also proposed to originate from low-mass AGB stars, but with metallicities lower than solar (Hoppe et al 1997;Amari et al 2001b). This low-metallicity scenario, however, was recently questioned (Liu et al 2019). The type C (∼0.1% of all SiC grains) and X grains (∼1% of all SiC grains) are believed to originate from core-collapse supernovae (CCSNe; Amari et al 1992;Hoppe et al 1996b;Gyngard et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The minor type Y and Z grains (a few % of all SiC grains, depending on grain size), which fall to the 30 Si-rich side of the Si mainstream line, were also proposed to originate from low-mass AGB stars, but with metallicities lower than solar (Hoppe et al 1997;Amari et al 2001b). This low-metallicity scenario, however, was recently questioned (Liu et al 2019). The type C (∼0.1% of all SiC grains) and X grains (∼1% of all SiC grains) are believed to originate from core-collapse supernovae (CCSNe; Amari et al 1992;Hoppe et al 1996b;Gyngard et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Vescovi et al [18], the same model was shown to be able to explain the most anomalous Mo isotope ratios of Y and Z grains, which are thought to have originated in lower-than-solar metallicity AGB stars and have Mo isotopic compositions indistinguishable from MS grains (see Liu et al [57] for more details). In this regard, however, recent analyses are revealing that the three groups of grains have also similar Sr and Ba isotopic compositions, thus questioning the low-metallicity stellar origin of Y and Z grains [58]. From the comparison with grain data, models computed with the REF data set seem to give a better match while models adopting the ASTRAL v0 set only provide a partial overlap.…”
Section: Resultsmentioning
confidence: 96%
“…Based on their Si and Ti isotopic compositions, Y and Z grains were previously inferred to have originated from low-mass AGB stars of 0.5 Z and 0.3 Z , respectively (Zinner et al 2007). However, Liu et al (2019) showed that these low-metallicity models adopted by Zinner et al (2007) cannot consistently explain the Mo isotopic compositions of Y and Z grains and that, more likely, Y and Z grains came from low-mass AGB stars of 0.7 Z . A small fraction of presolar SiC, including X and possibly AB grains, also came from ancient Type II supernovae (Zinner 2014;Liu et al 2017a;Hoppe et al 2019).…”
Section: Introductionmentioning
confidence: 96%